The Impact of Profitability of Hospital Admissions on Mortality. (24th January 2013) - Lindrooth, Richard C.; Konetzka, R. Tamara; Navathe, Amol S.; Zhu, Jingsan; Chen, Wei; Volpp, Kevin
Abstract : Background: Fiscal constraints faced by Medicare are leading to policies designed to reduce expenditures. Evidence of the effect of reduced reimbursement on the mortality of Medicare patients discharged from all major hospital service lines is limited. Methods: We modeled risk‐adjusted 30‐day mortality of patients discharged from 21 hospital service lines as a function of service line profitability, service line time trends, and hospital service line and year‐fixed effects. We simulated the effect of alternative revenue‐neutral reimbursement policies on mortality. Our sample included all Medicare discharges from PPS‐eligible hospitals (1997, 2001, and 2005). Results: The results reveal a statistically significant inverse relationship between changes in profitability and mortality. A $0.19 average reduction in profit per $1.00 of costs led to a 0.010–0.020 percentage‐point increase in mortality rates ( p  < .001). Mortality in newly unprofitable service lines is significantly more sensitive to reduced payment generosity than in service lines that remain profitable. Policy simulations that target service line inequities in payment generosity result in lower mortality rates, roughly 700–13, 000 fewer deaths nationally. Conclusions: The policy simulations raise questions about the trade‐offs implicit in universal reductions in reimbursement. The effect of reduced payment generosity on mortality could be mitigated by targeting highly profitable services only for lower reimbursement.